Combined volumetric, energetic and microstructural defect analysis of ECAP-processed nickel. (15th January 2016) - Reglitz, Gerrit; Oberdorfer, Bernd; Fleischmann, Nina; Kotzurek, Jaromir Anatol; Divinski, Sergiy V.; Sprengel, Wolfgang; Wilde, Gerhard; Würschum, Roland
Abstract: Difference dilatometry and differential scanning calorimetry (DSC) are used to investigate defect annealing in ultrafine grained nickel processed by equal channel angular pressing (ECAP) at various temperatures. Different defect types and processes such as vacancies, dislocations, grain boundaries and grain-boundary relaxation can be detected. They can be distinguished due to their distinct kinetics as revealed by the release of excess volume and excess heat during linear heating. The data are quantified in combination with a detailed characterization of the microstructure. Values for the absolute vacancy concentration, the dislocation density, the grain boundary expansion and the excess of grain boundary expansion in ECAP-processed nickel are derived. Graphical abstract: Highlights: Defect annealing in UFG nickel is investigated by difference dilatometry and DSC. Detailed characterization of the microstructure allowed to quantify the data. Vacancy concentration, dislocation density, grain boundary expansion and excess of grain boundary expansion are determined.